1985
DOI: 10.1111/j.1600-0447.1985.tb02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum melatonin in relation to clinical variables in patients with major depressive disorder and a hypothesis of a low melatonin syndrome

Abstract: Maximum nocturnal serum melatonin level (MTmax) in relation to some clinical variables was studied in 32 patients with a major depressive episode and in 33 healthy subjects with reference to the outcome of the dexamethasone suppression test (DST). Significant regressions were found between MTmax levels and clinical rating scores in CPRS, interpreted as retardation symptoms. Four healthy subjects with disposition for dysthymic reactions had subnormal MTmax levels, which differed from MTmax levels in subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(74 citation statements)
references
References 38 publications
(17 reference statements)
2
71
0
Order By: Relevance
“…Abnormally low melatonin levels are found in major depression (Beck-Friis et al 1985) and correlate with depressive symptom severity in patients with anorexia nervosa (Kennedy et al 1989) and premenstrual dysphoric disorder (Parry et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormally low melatonin levels are found in major depression (Beck-Friis et al 1985) and correlate with depressive symptom severity in patients with anorexia nervosa (Kennedy et al 1989) and premenstrual dysphoric disorder (Parry et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, early evening administration of melatonin has been found to decrease sleep latency and increase sleep efficiency in the elderly (Zhdanova et al 2001) and in patients with primary insomnia (Garfinkel et al 1995;Haimov et al 1995;Zhdanova et al 1995;Girardin et al 1998) but have no effects on measures of sleep architecture or REM sleep (Zhdanova et al 2001). Likewise, in older adults and psychiatric populations such as depressed patients, melatonin onset and/or peak values are altered in association with disturbances of sleep continuity (Nair et al 1984;Beck-Friis et al 1985;Kennedy et al 1989;Dijk et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In as early as 1985, it was proposed that depression might be a syndrome with low melatonin [83] , characterized by low levels of melatonin at night, abnormal dexamethasone suppression, and disorder of the 24-h cortisol rhythm. A cross-sectional study in 2012 further supported the low melatonin hypothesis [84] by showing that nocturnal melatonin levels in patients with depression are signifi cantly lower than in controls.…”
Section: The Circadian Rhythm Disorder Hypothesis and New Targets Formentioning
confidence: 99%
“…Our results, showing lower platelet 5-HT levels in depressed patients compared to healthy control subjects within the same period, could be a direct consequence of the altered melatonin production and/or disruption of melatonin's biological functions present in depressive disorders. Although in our study we did not measure the plasma melatonin levels, literature data shows increased secretion of melatonin in depressed patients [14][15][16][17][18], suggesting an interaction of melatonin with the 5-HT system.…”
Section: Discussionmentioning
confidence: 97%
“…Melatonin regulates biological rhythms and levels of biomolecules that exert various peripheral actions, thus affecting many critical processes [13]. Various studies have shown altered melatonin secretion in depression [14][15][16][17][18][19], seasonal affective disorder (SAD) [20][21], schizophrenia [22][23][24][25][26], panic disorder [27], obsessive-compulsive disorder [17,28] and Alzheimer's disease [29], suggesting an interaction of melatonin with the central neurotransmitter systems. Goergen et al (2002) have shown that light-controlled rhythm could be the primary regulator of neuronal proliferation and that previously demonstrated hormonal and activitydriven influences over neurogenesis may be the secondary events in a complex circardian control pathway [30].…”
Section: Introductionmentioning
confidence: 99%